Flavor dependence of charged pion fragmentation functions - H. Bhatt; P. Bosted; S. Jia; W. Armstrong; D. Dutta; R. Ent; D. Gaskell; E. Kinney; H. Mkrtchyan; S. Ali; R. Ambrose; D. Androić; et al. (Physics Letters B)
We have measured the flavor dependence of multiplicities for π+ and π− production in semi-inclusive deep-inelastic scattering (SIDIS) on proton and deuteron to explore a possible charge symmetry violation in fragmentation functions. The experiment used an electron beam with energies of 10.2 and 10.6 GeV at Jefferson Lab and the Hall-C spectrometers. The electron kinematics spanned the range 0.3<x<0.6, 2<Q2<5.5 GeV2, and 2.2<W<3.2 GeV. The pion fractional momentum range was 0.3<z<0.7, and the transverse momentum range was 0<pT<0.25 GeV/c. Assuming factorization and allowing for isospin breaking, the results can be described by two “favored” and two “unfavored” effective low pT fragmentation functions that are flavor-dependent. We find each pair converges to a common flavor-independent fragmentation function at the highest W, where factorization is most applicable.